Legal education in the digital age / edited by Edward Rubin. - Rubin, Edward L., 1948- (Cambridge University Press, 2012)
During the coming decades, the digital revolution that has transformed so much of our world will transform legal education as well. The digital production and distribution of course materials will powerfully affect both the content and the way materials are used in the classroom and library. This collection of essays by leading legal scholars in various fields explores three aspects of this coming transformation. The first set of essays discusses the way digital materials will be created and how they will change concepts of authorship as well as methods of production and distribution. The second set explores the impact of digital materials on law school classrooms and law libraries and the third set considers the potential transformation of the curriculum that the materials are likely to produce. Taken together, these essays provide a guide to momentous changes that every legal teacher and scholar needs to understand.